IMPLEMENTASI ISOMETRIC HANDGRIP EXERCISE DALAM MENURUNKAN TEKANAN DARAH PADA PASIEN DENGAN HIPERTENSI : STUDI KASUS - Qonita Huwaida; Ani Syafriati; Yuasti Ningsih (LPPM STIKes Mitra Adiguna, 2026)
Hypertension is one of the health problems that often occur in the elderly and is the main risk factor for heart disease and stroke. The management of hypertension is not only carried out with pharmacological therapy, but also through non-pharmacological interventions such as physical exercise. One of the exercises that is easy to do is the isometric handgrip exercise which can lower blood pressure through increased vascular tone and adaptation of the autonomic nervous system. This study is a case study on four hypertensive patients, namely Mrs. M (72 years old), Mrs. S (69 years old), Mr. J (50 years old), and Mr. S (54 years old). The intervention was carried out by measuring blood pressure before and after isometric handgrip exercises for 4 minutes with a 30-second break while taking deep breaths. The results showed a decrease in blood pressure in most patients, namely in Mrs. M from 217/57 to 214/74 mmHg, Mrs. S from 143/76 to 141/73 mmHg, and Mr. S from 173/108 to 166/131 mmHg, while Mr. J experienced an increase in blood pressure after exercise. Overall, this exercise has a positive effect on blood pressure stability. Isometric handgrip exercise can be used as a simple and effective non-pharmacological intervention in the management of hypertension.